2015
DOI: 10.1371/journal.pone.0133286
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Interval Training Improves Glycaemic Control and Pancreatic β Cell Function of Type 2 Diabetes Patients

Abstract: Physical activity improves the regulation of glucose homeostasis in both type 2 diabetes (T2D) patients and healthy individuals, but the effect on pancreatic β cell function is unknown. We investigated glycaemic control, pancreatic function and total fat mass before and after 8 weeks of low volume high intensity interval training (HIIT) on cycle ergometer in T2D patients and matched healthy control individuals. Study design/method: Elderly (56 yrs±2), non-active T2D patients (n = 10) and matched (52 yrs±2) hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
112
1
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(152 citation statements)
references
References 84 publications
23
112
1
16
Order By: Relevance
“…Inconsistent with recent studies showing improved firstphase DI following HIIT but not MICT in type 2 diabetic patients [48,53], our study only showed a significant basal DI improvement following MICT in MetS individuals with type 2 diabetes. This improvement resulted from increased insulin sensitivity with no accompanying change in insulin secretion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Inconsistent with recent studies showing improved firstphase DI following HIIT but not MICT in type 2 diabetic patients [48,53], our study only showed a significant basal DI improvement following MICT in MetS individuals with type 2 diabetes. This improvement resulted from increased insulin sensitivity with no accompanying change in insulin secretion.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with our study wherein no significant improvement in either fasting intact proinsulin concentration or HbA 1c was evident in a subgroup of MetS participants with type 2 diabetes following any of the exercise interventions. In contrast, other studies have demonstrated a significant HbA 1c improvement following 8-12 weeks of HIIT in type 2 diabetic patients [48,49], which could be attributed to the difference in pre-existing glycaemic status of individuals within each study. Indeed, Malin et al [50] showed that individuals with a combination of IFG and IGT were less responsive to exercise-induced improvement in insulin sensitivity relative to individuals with IGT alone at baseline.…”
Section: Discussionmentioning
confidence: 58%
“…In accordance, Madsen et al [21,22] reported that an 8-week HIIT training (strenuous bicycle exercise) had induced improvement in circulating omentin, together with abdominal fat mass loss and enhanced glycemic control in middle-aged type 2 diabetics. However, Nikseresht et al [23] showed no change in omentin after 12 weeks of moderate interval training in middle-aged obese men.…”
Section: Discussionmentioning
confidence: 67%
“…High-intensity interval training (HIIT) that alternates high-intensity periods of work and periods of rest has gained attention as time-efficient and effective method for improving cardiorespiratory fitness and reducing cardiometabolic risks [20,21]. To date, only few studies examined the response of omentin to interval training in diabetic adults and individuals at high metabolic risk [22] as well as in middle-aged obese men [23].…”
Section: Introductionmentioning
confidence: 99%
“…Estos últimos trabajos citados no han incluido intervención en los niveles de actividad física de sus participantes para facilitar el posterior análisis de los resultados. Es necesario mencionar que en lo que se refiere a la actividad física existe un cuerpo sólido de evidencia que demuestra que la actividad muscular disminuye la resistencia central, periférica y vascular a la insulina logrando mejorías significativas en la función pancreática y en el grado de control de la enfermedad 14,15 .…”
unclassified